Pengaruh corporate governance, dan faktor-faktor lainnya terhadap manajemen laba - FRISKA FIRNANTI (Jurnal Bisnis dan Akuntansi, 2017)
The objective of this research is to obtain empirical evidence of board of independence, institutional ownership, board of size, managerial ownership, profitability, firm size, audit quality, audit committee, and leverage as independent variables to earnings management. Earning management as dependent variable in Indonesian manufacturing companies.The research period is three years from 2012-2014 and population in this research is all listed companies in Indonesian Stock Exchange. Samples are obtained through purposive sampling method, listed manufacturing companies in Indonesian manufacturing companies meet the sampling criteria, resulting 185 data. Multiple linear regressions is used as the data analysis method in this research.The result of this research shows that profitability, firm size, audit quality, and leverage statistically have effect on the earningsmanagement. While other variables such as board of independence, institutional ownership, board of size, managerial ownership, and audit committee have no effect on earnings management.